Compact dual polarised V slit, stub and slot embedded circular patch antenna for UMTS/WiMAX/WLAN applications. Issue 17 (1st August 2016) - Mathew, S.; Ameen, M.; Jayakrishnan, M.P.; Mohanan, P.; Vasudevan, K.
Abstract : A single probe‐fed novel V slit, stub and slot embedded circular microstrip antenna with resonances in the three bands of UMTS, worldwide interoperability for microwave access (WiMAX) and WLAN is presented. The polarisation is circular in the UMTS band and linear in the other two bands. Asymmetrical V slits in the patch boundary along with an embedded circular slot in the patch centre are employed to introduce the perturbation necessary for circular polarisation. Impedance bandwidths (BWs) of 4.2, 2 and 6.2%, respectively, in the three bands centred at 2, 3.5 and 5.6 GHz are obtained. The axial ratio BW is 2.3% in the UMTS band. Moderate gains of 4.4, 3.5 and 2.8 dBi are obtained in the three bands. There is a patch size reduction of about 48% when compared with the conventional circular patch antenna at a fixed operating frequency. The radiation pattern is directional in the WiMAX band and nearly omnidirectional in the WLAN band.